2008
DOI: 10.1371/journal.pcbi.1000071
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Sequence Motifs with Arbitrary Insertions and Deletions

Abstract: Biology is encoded in molecular sequences: deciphering this encoding remains a grand scientific challenge. Functional regions of DNA, RNA, and protein sequences often exhibit characteristic but subtle motifs; thus, computational discovery of motifs in sequences is a fundamental and much-studied problem. However, most current algorithms do not allow for insertions or deletions (indels) within motifs, and the few that do have other limitations. We present a method, GLAM2 (Gapped Local Alignment of Motifs), for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
290
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(290 citation statements)
references
References 58 publications
0
290
0
Order By: Relevance
“…8). In addition, we used this motif to query the entire E. coli K12 proteome by GLAM2SCAN (30). The result showed that the top ten ranking proteins containing this motif were identical to our identified proteins (Table IV).…”
Section: Ds][vq][dte]a [Yil]x[ak][arl][mv][etk][lv]mentioning
confidence: 84%
See 3 more Smart Citations
“…8). In addition, we used this motif to query the entire E. coli K12 proteome by GLAM2SCAN (30). The result showed that the top ten ranking proteins containing this motif were identical to our identified proteins (Table IV).…”
Section: Ds][vq][dte]a [Yil]x[ak][arl][mv][etk][lv]mentioning
confidence: 84%
“…Motif Search with GLAM2-All identified proteins were converted to FASTA format and analyzed by Gapped Local Alignment of Motifs (GLAM2) (30) for surveying consensus motif. The parameters of GLAM2 were set as default.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed and precized study of aptamer-apatope interaction and evolutionary processes induced by the interplay lag behind the wide application of the SELEX products [13]. The binding property of aptamer is a func-* Corresponding author.…”
Section: Introductionmentioning
confidence: 99%